(untitled) (Research, Society and Development, 2020)
The lack of patient safety in the use of medicines constitutes a worldwide health problem, increasing the concern around policies aimed at improving quality and care safety. The objective of this work is to know the methodologies used for teaching in undergraduate health on safety in the use of medicines. The methodology used was an integrative review of articles published between January/2014 and June/2019 that present teaching methodologies for undergraduate health on safety in the use of medicines. Thirty-five articles were selected. The themes on medication administration (n=11) and calculation of medication dose (n=6) were the most addressed, specifically for nursing undergraduates. The theme "prescription of medicines" (n=4) was addressed by medical students. The safety of the medication was addressed in four studies. The main methodologies identified were: simulation, problem-based learning and multimedia. It is concluded that the methodology to be applied in teaching the safe use of medicines depends on the context of the student and health services, as well as on the learning objectives. Clinical reasoning and critical thinking regarding the safe use of medicines should be practiced during the undergraduate teaching of health courses.